2005
DOI: 10.1375/ajgc.15.2.182
|View full text |Cite
|
Sign up to set email alerts
|

Approaches to Children, Young People and Mental Health: Confusion in the Ranks, Confusion Among the Commanders

Abstract: The need to provide support for the mental health needs of children and young people is not in dispute. However, there does exist confusion as to the most appropriate means and methods of providing such support. This confusion is particularly evident among those who work closely in providing daily for the mental health needs of children and young people, yet who lack specific mental health training. The confusion is heightened by the fact that those who have developed expertise in mental health cannot offer a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2011
2011

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…Other studies have confirmed this challenge for teachers (Pine, Cohen, Cohen, & Brook, 1999). Murray (2005) argues that the ambiguity between normal adolescent behaviour and mental health problems is heightened by confusion and lack of consensus about the most appropriate methods of providing support. She asks if we are pathologising the normal ups and downs of life.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have confirmed this challenge for teachers (Pine, Cohen, Cohen, & Brook, 1999). Murray (2005) argues that the ambiguity between normal adolescent behaviour and mental health problems is heightened by confusion and lack of consensus about the most appropriate methods of providing support. She asks if we are pathologising the normal ups and downs of life.…”
Section: Discussionmentioning
confidence: 99%